Demography and Human Capital: Why Education Matters - Abad, Ricardo G (Archīum Ateneo, 2020)
In this lecture, Dr. Abad discusses demography and human capital, looking at how education affects a country's population growth and overall resiliency. Speaker: Dr. Ricardo Abad, Areté’s Artistic Director, is also Professor Emeritus of the Ateneo de Manila University with joint appointments at the Department of Sociology and Anthropology and the Theater Arts Program, Department of Fine Arts. He is also President of the Asia-Pacific Bond of Theater Schools; Board Member of the Asian Shakespeare Association, Senior Fellow of the Social Weather Stations, and past president of the Philippine Sociological Society. He has received several recognitions, among them the Metrobank Outstanding Teaching Award, the Asian Public Intellectual Fellowship, and the Golden Leaf Award for Theater Education. His scholarly works have appeared in Kritika Kultura, Philippine Studies, Philippine Sociological Review, Perspectives in the Arts and Humanities Asia, Population and Environment, and Shakespeare’s Asian Journeys (Routledge, 2017).